STUDY OF A SOLAR ENERGY KALINA CYCLE APPLIED IN BOM JESUS DA LAPA - BAHIA - Amorim, G. S.; Sato, A. I.; Souza, A. B.; Rodrigues, V. M. (Revista de Engenharia Térmica, 2023)
Modern population’s needs increased demands for electricity in such a way that new energy sources were explored, in search of lower environment impacts and fossil fuels dependency. Renewable energy sources for electricity production, such as solar and wind energy, have significantly attracted attention and places as the west region of Bahia state has a good potential for its application. This location is characterized by high solar irradiance of 2136 kWh/m² a year, already having 4 photovoltaic power plants in operation and 2 more in project phases. Another possible application is the solar thermal energy and Kalina Cycle presents as a good possibility for employing it, since the non-azeotropic mixture of ammonia-water as working fluid allows low temperature heat sources utilization. Based on that, this research proposed the study of a Kalina power cycle, with steady state conditions, using thermal solar energy as low temperature heat source and applied to the solar irradiance of Bom Jesus da Lapa – BA. The thermodynamic cycle was developed and simulated with Engineering Equation Solver (EES®), thermal efficiency was analyzed by varying parameters such as: heat source temperature from 90 °C to 120 °C, high pressure line from 10 to 35 bar and ammonia mass fraction from 0.35 to 0.95. The final cycle presented a superheater before the turbine and a regenerator with poor ammonia-water mixture from the separator (as hot side) and ammonia-water mixture before entering the boiler (as cold side). Results indicated maximum efficiency of 7.4%, with high pressure side of 35 bar, heat source temperature of 120 °C, superheater heat source temperature of 200 °C and ammonia mass fraction of 0.64 kg/kg.